Statistical methodologies for determining critical parameters in a pick-and-place process on a surface mount device line - S. Lima; L. Silva; A. Manuela Gonçalves; M. T. Malheiro; M. Pinhão; J. Machado; J. Meireles; A. J. Pontes (Research in Statistics)
Surface mount technology (SMT) involves assembling surface mount devices (SMDs) using automated SMD placement machines (SMDPMs) to place SMDs onto the substrate’s surface with pick-and-place units. The SMDPMs are fully automated and high-speed, often representing a bottleneck in assembly lines. One primary cause of component rejection and assembly defects is vacuum loss. The goal of this study is to understand the vacuum system operation and the relationship between heads and nozzles to identify inherent vacuum losses in pick-and-place machines. Vacuum losses can be assessed through variations in air flow or air pressure. This article experimentally investigates nozzle flow using a full factorial design. Significant factors affecting pick-and-place performance were evaluated using nonparametric methods. The findings indicate that both air flow and air pressure are independent of the nozzle’s position on the machine head. Adjacent nozzles showed no effect on air flow, while air pressure depends on the number of uncovered nozzles in the machine. Additionally, it was observed that leaks of identical sizes can have varying impacts depending on the head model. Practically, leaks in one component can affect the vacuum available for transporting other components, leading to higher rejection rates or incorrect placements.